Alcohol Medical Intervention Clinic: A Rapid Access Addiction Medicine Model Reduces Emergency Department Visits. Issue 2 (March 2020) - Corace, Kimberly; Willows, Melanie; Schubert, Nicholas; Overington, Louise; Mattingly, Sean; Clark, Eric; Leduc, Nathaniel; Hutton, Brian; Hebert, Guy
Abstract : Objectives: Problematic alcohol use accounts for a large proportion of Emergency Department (ED) visits and revisits. We developed the Alcohol Medical Intervention Clinic (AMIC), a Rapid Access Addiction Medicine (RAAM) service, to reduce alcohol-related ED re-utilization and improve care for individuals with alcohol problems. This article describes the AMIC model and reports on an evaluation of its impact on patients and the ED system. Methods: Individuals presenting to The Ottawa Hospital Emergency Departments (TOH-ED) for an alcohol-related issue were referred to AMIC. Using data collected via medical chart review, and also self-report questionnaires, we assessed ED visits, revisits, and changes in alcohol use and mental health symptoms in patients before and after receiving services in AMIC. The incidence of alcohol-related ED visits and re-visits from 12-month periods before and after the introduction of AMIC were compared using data from TOH Data Warehouse. Connections made to additional services and patient satisfaction was also assessed. Results: For patients served by AMIC, from May 26, 2016 to June 30, 2017 (n = 194), there was an 82% reduction in 30-day visits and re-visits ( P < 0.001). An 8.1% reduction in total alcohol-related 30-day TOH-ED revisit rates and a 10% reduction in total alcohol-related TOH-ED visits were found. After receiving AMIC services, clients reported reductions in alcohol use, depression, and anxiety ( P < 0.001). Conclusions: AMIC demonstrated positive impacts on patients and the healthcare system. AMIC reduced ED utilization, connected people with community services, and built system capacity to serve people with alcohol problems.